Experimental and population-genetic evidence for inflammation control functions of long noncoding RNAs and a novel tRNA-like transcript arising from the human NEAT1-MALAT1 genomic region. (25th November 2020) - Poller, C; Kuss, A.W; Weiss, S; Haghikia, A; Gast, M; Mochmann, L; Zeller, T; Blankenberg, S; Felix, S; Voelker, U; Doerr, M; Voelzke, H; et al.
Abstract: Background: Uncontrolled inflammation is a key driver of atherosclerosis, myocardial infarction (MI), and multiple other diseases. Beyond proteins and microRNAs, long noncoding RNAs (lncRNAs) are implicated in inflammation control. We previously reported suppression of lncRNA NEAT1 in circulating immune cells of post-MI patients. In mice lacking lncRNAs NEAT1 or MALAT1 we observed major immune disturbances affecting monocyte-macrophage and T cell differentiation and rendering the immune system unstable and highly vulnerable to immune stress. Here, we report functions of a novel tRNA-type transcript arising from the NEAT1-MALAT1 gene cluster, and on genetic heterogeneity of this region in the human population. Methods and results: While previously investigated mice were deficient in the entire NEAT1 or MALAT1 locus, we here aimed to selectively disrupted only the novel 59-nt tRNA-like transcript "menRNA" with hitherto unknown functions. Through CRISPR/Cas9 editing we developed 4 human THP-1 monocyte-macrophage cell line clones with deletions of different extension all of which prevented, however, normal transcript folding and formation of "menRNA". Transcriptome mapping of all clones by RNA-sequencing identified dysregulation of innate immunity-related genes (IFI16, IFITM3, IRAK3, IRF2BP2, IRF3), chemokine and interleukin receptors (CCR10, IL11RA, IL12RB2, IL23A), cell surface receptors (CD37, CD40LG, CD72, FOCAD, ITGA6, MAEA, THY1), macrophage function-associated genes (ELANE, GRN, MIF, MMP25, MST1P2, PRTN3), tRNA-processing transcripts (GARS, QRSL1P3, QTRT1P1, THG1L, VARS), and small nucleolar RNAs (SNORA26.62.64, SNORD65.112). These data and functional assays indicate functions of NEAT1-derived "menRNA" distinct from those previously described for MALAT1-derived mascRNA. As multiple data suggest inflammation control functions of the NEAT1-MALAT1 region, we investigated the extent of genetic variability of this region in humans. In cohorts from the SHIP study coordinated by the Institute for Community Medicine Greifswald, screening of this region for sequence variants and possible phenotype associations was conducted the results of which are given in Figure 1. Consistent with prior findings, a MALAT1 SNP with very low minor allele frequency (MAF=0.01) was associated (p=0.0062) with systemic low level inflammation (CRP >3.0 mg/L). Unexpected was the association (p<0.01) of eight SNPs (low MAF=0.09 for all) with BMI >35 kg/m 2 and LDL >164 mg/dl. Conclusions: First, selective disruption of menRNA formation in human monocyte-macrophages provides evidence that this novel type of noncoding RNA has immunoregulatory functions. Second, the phenotype associations of SNPs within the NEAT1-MALAT1 gene cluster warrant further in-depth investigation of the molecular basis of these associations, and of their allele frequencies in cardiovascular disease patient cohorts. The first three and the last authors contributed equally to this work. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): "Transcriptome analysis of circulating immune cells to improve the assessment of prognosis and the response to novel anti-inflammatory treatments after myocardial infarction"; DZHK Shared Expertise project B19-006_SE FKZ 81X2100257